1987
DOI: 10.2320/matertrans1960.28.120
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Cycling Effect in Cu&ndash;Zn&ndash;Al Shape Memory Alloys with B2 and D0<SUB>3</SUB> Type Ordered Structures in Parent Phase

Abstract: Effect of thermal cycling on the martensitic transformation in two kinds of Cu-Zn-Al shape memory alloys, whose parent phases are ordered into D03 and B2 types, has been examined by electrical resistivity vs. temperature measurement, optical and transmission electron microscopy and X-ray diffraction. The thermal cycling was carried out between 77 K below Mf temperature and 288 K above Af temperature up to 104 times. With increasing thermal cycle, Ms temperature of the B2 type alloy (Cu-29.1Zn-6.7Al (at.%)) inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The temperatures marked by an asterisk are associated with the transformation of an amount of material already detectable by other techniques, and we can thus compare our results to those obtained using other less sensitive techniques, such as electrical resistivity measurements. Tadaki et a1 [4], studying samples quenched at 263 K, have reported that for DO3 ordered Cu-Zn-A1 (as is the case for our samples) the M , temperature decreases with thermal cycling. This is the same behaviour observed for our M,* and indicates that the electrical resistivity has insufficient resolution to detect the very smooth transformation beginning.…”
Section: Transformation Temperaturessupporting
confidence: 70%
See 1 more Smart Citation
“…The temperatures marked by an asterisk are associated with the transformation of an amount of material already detectable by other techniques, and we can thus compare our results to those obtained using other less sensitive techniques, such as electrical resistivity measurements. Tadaki et a1 [4], studying samples quenched at 263 K, have reported that for DO3 ordered Cu-Zn-A1 (as is the case for our samples) the M , temperature decreases with thermal cycling. This is the same behaviour observed for our M,* and indicates that the electrical resistivity has insufficient resolution to detect the very smooth transformation beginning.…”
Section: Transformation Temperaturessupporting
confidence: 70%
“…The thermal or mechanical cycling of shape-memory alloys has been reported to modify the transformation characteristics. In particular, for Cu-Zn-A1 alloys different experimental techniques, such as electrical resistivity [3,4] and differential scanning calorimetry [5,6,71, have been used to analyse such effects, leading to results which seem not to be coincident. Until now, the evolution of the thermodynamic magnitudes involved in the thermoelastic transformation has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is supposed that in Cu-Zn-Al alloys with a low T B2-DO 3 ðL2 1 Þ c temperature (<600 K), the crystal structure of the b phase in the quenched state is the B2 structure. Actually, it has been reported that a Cu 64.2 Zn 29.1 Al 6.7 alloy with a low T B2-DO 3 ðL2 1 Þ c temperature has the B2 structure in the quenched state [32]. Kuper et al [33] reported that the activation energy for self-diffusion in a Cu-(47-48) at.% Zn alloy (b brass) single crystal with the B2 structure in the temperature range 537-654 K, determined using Cu 64 and Zn 65 as the tracer elements, was $150 kJ mol À1 .…”
Section: Kinetics Of Bainitic Transformationmentioning
confidence: 99%
“…In the Cu-Zn-Al system, an FCC Cu-based solid solution phase, α, can coexist with austenite β ( [38], B2 [38,39] or structure depending on composition and thermal processing [40]), as can be seen in a vertical section at 4 wt% Al of the Cu-Zn-Al phase diagram in Fig. 2(c), where the chosen alloy composition is shown as the red dashed line.…”
mentioning
confidence: 99%